Faktor risiko perdarahan pasca persalinan primer - Ningsih, Ari Arfian; Sujiyatini, Sujiyatini; Zein, Asmar Yetti (Jurnal Kesehatan Ibu dan Anak, 2020)
Maternal mortality in of Yogyakarta in 2013 caused by bleeding ( 33%). Bleeding post delivery piece is themost primary of obstetric haemorrhage as the cause ofmaternal death. Risk factors of bleeding post delivery primer i.e. age, parity, anemia, medical disease, induction of iabor. childbirth, episiotomy, duration and amniotic rupture early. There has been increasing bleeding scene in the aftermath of a primary in childbirth rsud wonosari. This research aims to get information about the risk of bleeding after a primary in childbirth rsud wonosari year 2014. This research descriptive research by adopting both cross sectionai. The population in this research is 47 mother who experienced postpartum hemorrhage after a primary in childbirth rsud wonosari 2014 as from 1 january 2014 to 31 december 2014. An instrument used in this research is check list. Data analysis univariabel displayed in a frequency distribution and the percentage of. Hasil penelitian faktorrisiko perdarahan pasca persalinan primer di RSUD Wonosari tahun 2014 adalah paritas pada multipara (64%), dan metode persalinan pervaginam(87,2%). Bleeding after childbirth primary occurred on the not with risk factors , which is aged 20-35 year (78.8 %) , not anemia (81%) , there is no medical disease (79%), not with induction (70,2%), the duration of normal delivery (38%), not episiotomi (85,1%) , and no amniotic broke early (85,1%) .